2021
DOI: 10.1093/intqhc/mzab050
|View full text |Cite
|
Sign up to set email alerts
|

Comparing length of hospital stay during COVID-19 pandemic in the USA, Italy and Germany

Abstract: Background COVID-19 is the most informative pandemic in history. These unprecedented recorded data give rise to some novel concepts, discussions, and models. Macroscopic modeling of the period of hospitalization is one of these new issues. Methods Modeling of the lag between diagnosis and death is done by using two classes of macroscopic analytical methods: the correlation-based methods based on Pearson, Spearman, and Kendall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
13
1
2
Order By: Relevance
“…A systematic review for patients LoS in COVID-19 [106] concluded that LoS in China was longer than any other country, which was referred to differences in criteria for admission and discharge, and different timing within the pandemic. In another study [105], a negative association between the LoS and the case fatality rate was found. Therefore, the estimation of the LoS can be introduced as a KPI to scale the success of the countries fighting the ongoing pandemic.…”
Section: The Time Dimension In Covid-19mentioning
confidence: 87%
See 1 more Smart Citation
“…A systematic review for patients LoS in COVID-19 [106] concluded that LoS in China was longer than any other country, which was referred to differences in criteria for admission and discharge, and different timing within the pandemic. In another study [105], a negative association between the LoS and the case fatality rate was found. Therefore, the estimation of the LoS can be introduced as a KPI to scale the success of the countries fighting the ongoing pandemic.…”
Section: The Time Dimension In Covid-19mentioning
confidence: 87%
“…A reason for that was the delays in COVID-19 testing results [104]. LoS in the USA was found to be 2 days more than that in Italy and 5 days less than that in Germany [105]. A systematic review for patients LoS in COVID-19 [106] concluded that LoS in China was longer than any other country, which was referred to differences in criteria for admission and discharge, and different timing within the pandemic.…”
Section: The Time Dimension In Covid-19mentioning
confidence: 99%
“…A reason for this was the delays in COVID-19 testing results [ 114 ]. The LOS in the USA was two days more than that in Italy and five days less than that in Germany [ 115 ]. A systematic review for patient LOS in COVID-19 [ 116 ] concluded that LOS in China was longer than that in any other country, referring to differences in criteria for admission and discharge and different timings within the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 , 16 , 18 , 20 , 22 A study using LoS to compare how well the USA, Italy, and Germany handled the pandemic at the beginning showed that the number of days between diagnosis and death varied significantly between the three countries. 23 Ours will be the first study to examine regional differences in factors related to hospital LoS in the SBU filling a crucial gap in knowledge needed to provide equitable high-quality healthcare across all four regions of the SBU.…”
Section: Introductionmentioning
confidence: 99%